Risk Factors and Outcome of Neonatal Hyperbilirubinemia: A Case Control Study in a Tertiary Level Paediatric Hospital - Afroze, Sharmin; Parvin, Ruma; nahar, Kamrun; Sultana, Razia; Rahman, Shyla; Ahmed, Erfan; Sonia, Sheikh Farjana; Sultana, Azmeri; Ghosh, Nobo Krishna; Begum, Nargis Ara; et al. (Dhaka Shishu (Children) Hospital Journal, 2022)
Introduction: Neonatal jaundice is one of the most common morbidities observed during the neonatal period. Several risk factors are responsible for this condition. Objective: This study was aimed to determine the possible risk factors and immediate outcome for jaundice in newborns. Methods: This case control study was performed over a period of 18 months (March 2019 -August 2020) in the Special Care Newborn Unit (SCANU) of Dr. M R Khan Shishu Hospital & Institute of Child Health (ICH). Risk factors for jaundice were evaluated by comparing cases with jaundice and controls having no jaundice. Results: A total of 230 neonates with jaundice and 250 neonates having no jaundice were enrolled. Maternal age between 31-40 years, less than 4 antenatal visits, primi, presence of maternal diabetes, babies born via caesarian section, small for gestational age, prematurity and intra-uterine growth restriction were significantly associated with jaundice in neonates (p value < 0.05). Multi-variate analysis revealed, babies with mothers having <4 antenatal visits were found to have 13 times more risk of developing jaundice than their matched controls (p= 0.00, CI= 0.78-14.9). Mean duration of phototherapy was longer for babies having jaundice due to blood group incompatibilities (4.82 ± 1.94). Most of the patients (91%) were discharged to home. Conclusion: Less than four antenatal visit is a significant risk factor for neonates to develop significant jaundice requiring treatment. Babies with blood group incompatibilities tend to require longer duration of phototherapy wherever most of the babies discharged to home with good recovery. DS (Child) H J 2021; 37(2): 109-115